Sustainable Valorization of Corncob Residues through Green Lignin Extraction for Functional Sunscreen Applications - Teguh Pambudi; Hilman Imadul Umam; Fajar Amelia Rachmawati Putri; Alifa Rahma Zuhri; Nanda Aurelia Salsabila S.; Melisa Nur Halimah; Sheryl Ayesha Bruning; Elzandra Imola Vioniken (Biology, Medicine, & Natural Product Chemistry, 2026)
Corncob residues represent an abundant agricultural biomass rich in cellulose, hemicellulose, and lignin. Lignin, an aromatic biopolymer containing benzene and ketone functional groups, exhibits inherent ultraviolet (UV) absorption, positioning it as a promising bio-based ingredient for sustainable sunscreen formulations. In this study, lignin was extracted from corncob residues—comprising 18.5% hemicellulose, 23.5% cellulose, and 16.5% lignin—using a green deep eutectic solvent (DES) system composed of choline chloride and citric acid, and benchmarked against conventional alkaline extraction using NaOH. FTIR analysis revealed attenuated peak intensities in DES-extracted lignin, indicating lower recovery and partial structural alteration relative to the NaOH-derived counterpart. Extraction yields were 10.06% for the DES method and 16.19% for the NaOH method. Sunscreen formulations containing 2%, 3%, and 4% lignin exhibited appreciable UV absorption, particularly within the UVA region, with the highest performance observed at 4% lignin loading. These results highlight the feasibility of valorizing corncob biomass through environmentally benign lignin extraction to produce functional bio-based materials for sustainable sunscreen applications.